Leptomeningeal enhancement under different MS immunotherapies: A monocentric retrospective cohort study of 214 patients. (January 2023) - Friedli, Christoph; Wagner, Franca; Hammer, Helly Noemi; Kamber, Nicole; Wiest, Roland; Diem, Lara; Chan, Andrew; Salmen, Anke; Hoepner, Robert
Background: Leptomeningeal inflammation in patients with multiple sclerosis (MS) mainly affects meningeal B-cell follicle-like structures linked to cortical and subpial lesions and can be visualized as leptomeningeal enhancement (LME). Objective: To evaluate the evolution of LME under different MS immunotherapies. Methods: A total of 214 MS patients treated with anti-CD20 therapies or fingolimod at the university hospital Bern were screened for LME. Magnetic resonance imaging (MRI) and medical records were retrospectively evaluated, and comparative statistics were applied. Results: We compared MS patients treated with anti-CD20 therapies (128 patients (59.8%)) or fingolimod (86 patients (40.2%)). Of 128 anti-CD20-treated patients, 108 (84.4%) had no LME, 11 (8.6%) had persistent LME, and 9 (7.0%) showed resolution of LME. Of 86 fingolimod-treated MS patients, 81 (94.2%) had no LME and 5 (5.8%) persistent LME. Patients with LME persistence were older than those without or resolution of LME ( p  = 0.039). Resolution of LME was more frequent during anti-CD20 compared with fingolimod treatment ( p  = 0.019). Conclusion: We observed LME resolution under treatment with anti-CD20 therapies. As LME might play an important role in cerebral gray matter pathology in MS, further investigations including extensions to higher field strengths, correlation with clinical phenotypes, and comparison with other immunotherapies are needed.